Penggunaan Bussiness Model Canvas (BMC) dalam Penetapan Strategi Pengembangan Perguruan Tinggi Maritim (Studi Kasus Pada Akademi Maritim Nusantara Cilacap) - Indriyani Indriyani; Altril Rayendra; Dhimas Rudy Hartanto; Tiara Pandan Sari (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
This study aims to determine the AMN development strategy through BMC and SWOT analysis. The research data uses primary data, while data collection is through observation, interviews and documentation. The results of this study are that the customer segments served are all people who wish to continue to higher education. AMN has adequate resources such as lecturers, educational staff and infrastructure. While the highest costs are training and personnel expenses with the largest income from cadets, the channels used as a means of information are websites, Facebook, Instagram, cooperation with shipping companies and other universities.